The weight of performance: Body fat percentage and physical fitness in Special Olympic basketball players - Gonzales, J. J.; Kesterson, M.; Snarr, R. L.; Thompson, M. D.; Melrose, D. (International Journal of Exercise Science Conference Proceedings, 2026)
Special populations include a variety of different conditions, including Down Syndrome, Autism, and Marfan`s Syndrome to name a few. Some conditions may have similar changes in Fat Mass (FM) and Fat Free Mass (FFM), while others have varying differences.